2013
DOI: 10.1038/bjc.2013.758
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring response to cytostatic cisplatin in a HER2(+) ovary cancer model by MRI and in vitro and in vivo MR spectroscopy

Abstract: Background:Limited knowledge is available on alterations induced by cytostatic drugs on magnetic resonance spectroscopy (MRS) and imaging (MRI) parameters of human cancers, in absence of apoptosis or cytotoxicity. We here investigated the effects of a cytostatic cisplatin (CDDP) treatment on 1H MRS and MRI of HER2-overexpressing epithelial ovarian cancer (EOC) cells and in vivo xenografts.Methods:High-resolution MRS analyses were performed on in vivo passaged SKOV3.ip cells and cell/tissue extracts (16.4 or 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 53 publications
(88 reference statements)
5
39
0
Order By: Relevance
“…13 This study suggested that MARCH1 regulates cellular processes, not only in immunity, but also in cell signal transduction. [22][23][24]36 Previous studies have shown an ADC increase following targeted agent treatment with cisplatin in an ovarian cancer model, 37 sorafenib in breast cancer xenografts 38 and irinotecan in colon carcinoma xenografts. In this regard, here, we demonstrated that MARCH1 deletion does affect the biomarker of HCC tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This study suggested that MARCH1 regulates cellular processes, not only in immunity, but also in cell signal transduction. [22][23][24]36 Previous studies have shown an ADC increase following targeted agent treatment with cisplatin in an ovarian cancer model, 37 sorafenib in breast cancer xenografts 38 and irinotecan in colon carcinoma xenografts. In this regard, here, we demonstrated that MARCH1 deletion does affect the biomarker of HCC tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The ADC value, as a non-invasive biomarker and a sensitive biomarker to predict early treatment responses in various malignant tumours derived from DW-MRIs, was used to assess tumour cellularity, necrosis, cell apoptosis and cell density. [22][23][24]36 Previous studies have shown an ADC increase following targeted agent treatment with cisplatin in an ovarian cancer model, 37 sorafenib in breast cancer xenografts 38 and irinotecan in colon carcinoma xenografts. 39 Hence, we used DW-MRI to monitor the therapy response of the HCC xenografts under different therapy conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ovarian cancer studies in mouse models use xenografts that are obtained either after subcutaneous implantation (19) or intraperitoneal injection of cancer cells (20). To mimic the tumor microenvironment, more recent models involved direct injection of cells into the ovarian intrabursa (21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the parental cell line, SKOV3.ip cells are characterized by a more aggressive phenotype, including faster in vivo tumor growth and increased overexpression of human epidermal growth factor receptor‐2 (HER2+++). These features, along with the already known EGFR++, HER3+/−, HER4+/−, p53‐null and PTEN+/− profile typical of the SKOV3 cells, are associated with a low responsiveness of SKOV3.ip cells to cisplatin …”
Section: Introductionmentioning
confidence: 90%
“…In vivo MRI technologies, including diffusion‐weighted MRI (DWI) and localized MRS, have been successfully applied by our group, shortly after the in vivo administration of either conventional or innovative drugs, for the identification of their induced functional changes and metabolic alterations in preclinical models, and even in the presence of tumor growth inhibition rather than tumor shrinkage . Clinical DWI applications also showed encouraging results in the imaging of a variety of gynecological cancer lesions …”
Section: Introductionmentioning
confidence: 99%